Leveraging Critical Proof Obligations for Efficient IC3 Verification - Zhu, Lingfeng; Zhang, Xindi; Li, Yongjian; Cai, Shaowei (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
IC3 and its variants are SAT-based model-checking methods that play a critical role in hardware verification. Efficient management of proof obligations, which track states that need to be proven unreachable, is essential for improving verification performance. This paper presents a novel approach that utilizes Critical Proof Obligations (CPOs) to improve proof obligation management. We propose two techniques, CPO-Driven UNSAT Core Generation and CPO-Driven Proof Obligation Propagation, to promote lemma propagation and frame refinement. Experimental results on HWMCC benchmarks demonstrate significant improvements in CPO discovery and lemma propagation, resulting in notable performance gains.